Effects of vaccination against foot-and-mouth disease virus on reproductive performance of Bos indicus beef cows - Ferreira, L. C. L.; Cooke, R. F. [UNESP]; Marques, R. S.; Fernandes, H. J.; Fernandes, C. E.; Stelato, R.; Franco, G. L.; Lemos, R. A. A. (Amer Soc Animal Science, 2016)
This study compared reproductive performance of Bos indicus cows vaccinated against the foot-and-mouth disease (FMD) virus before timed AI or during early pregnancy (Exp. 1), as well as rectal temperature (RT) and plasma concentrations of the acute-phase protein haptoglobin in cattle vaccinated or not against the FMD virus (Exp. 2). Cattle utilized in Exp. 1 and 2 originated from herds with no historical occurrences of FMD and that received vaccination against the FMD virus biannually. In Exp. 1, 604 lactating, multiparous, nonpregnant Nelore cows were randomly assigned on d -31 of the experiment to receive 1) vaccination against the FMD virus on d >= 31 (VACPRE; n = 291) and 2) vaccination against FMD virus on d 30 (VACGEST; n = 313). From d -11 to 0, all cows were assigned to an estrus synchronization + timed AI (d 0) protocol. Pregnancy status to AI was verified on d 30 and 90 via transrectal ultrasonography. A treatment x day interaction was detected (P < 0.01) for pregnancy rates to AI, which were similar (P = 0.17) between VACPRE and VACGEST on d 30 (61.8% vs. 56.2%, respectively; SEM = 2.8) but greater (P < 0.01) for VACPRE on d 90 (59.4% vs. 46.9%, respectively; SEM = 2.8). Pregnancy loss from d 30 to 90 was greater (P < 0.01) in VACGEST compared with VACPRE (16.5% vs. 3.9%, respectively; SEM = 2.2). In Exp. 2, 40 pregnant Nelore females (20 nulliparous and 20 multiparous cows; BCS = 4.73 +/- 0.12) were ranked by parity and assigned to receive (VAC; n = 20) or not receive (NOVAC; n = 20) vaccination against the FMD virus. Blood samples were collected and RT was recorded before (h 0) and 24, 72, 120, and 168 h after treatment administration. Treatment x day interactions were detected (P < 0.01) for RT and plasma haptoglobin. The RT was greater (P < 0.01) in VAC compared with NOVAC at 24 h after treatment administration and was similar (P = 0.31) between treatments at all other sampling hours. Plasma haptoglobin concentration was similar (P = 0.98) between VAC and NOVAC before treatment administration (P = 0.48) and greater (P < 0.01) in VAC at 24, 72, 120, and 168 h after treatment administration. In summary, vaccinating B. indicus beef cows against the FMD virus resulted in a 4-fold increase in pregnancy loss when the vaccine was administered 30 d after timed AI compared with 31 d before timed AI. These outcomes can be associated with inflammatory and acute-phase reactions elicited by the FMD vaccine, which are known to impair pregnancy maintenance in cattle.
Keywords: acute-phase response; beef cattle; foot-and-mouth disease; inflammation; pregnancy loss